KONSEP KEPEMIMPINAN DALAM PRESPEKTIF ISLAM - Putri, Diya (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2020)
Talking about educational leadership in Islam, we can not be separated from the footsteps of the Prophet Muhammad SAW who is the leader of humanity. Leadership is a strength thath is in a leader who drives a person’n activities to achieve success. While education is a process with certain methods so that people will gain knowledge, understanding, and how to behave in accordance with needs. In the life of Islamic society today many forget and leave the element of educational leadership that was taught by the Prophet Muhammad SAW to his people. Because, as a leader thaht is exemplary and can be used as an example for the leadership of its members, the Messenger of Allah is also given four qualities so that it can be an example to his people, namely: Siddiq, Amanah, Tabligh, Fathanah. Siddiq which means honest in words and deeds, Amanah which means can be trusted in maintaining responsibility, Tabligh which means conveying all kindness to its members, and Fathanah which means intelligent in managing his leadership.